THE ROLE OF AMBIDEXTERITY IN MEDIATING ENTREPRENEURIAL ORIENTATION AND BUSINESS PERFORMANCE IN SMES - Indra Prasetyo; Rusdiyanto Rusdiyanto; Nur Fadjrih Asyik; Nabilah Aliyyah; Rahmat Luthfi Haidar; Adiba Fuad Syamlan (Фінансово-кредитна діяльність: проблеми теорії та практики)
This study delves into the mediating role of organizational ambidexterity in the relationship between entrepreneurial orientation and business performance among small and medium-sized enterprises (SMEs) in East Java, Indonesia. By employing a quantitative research design, data were meticulously gathered from 200 SME respondents through a semi-structured questionnaire, ensuring a broad yet detailed representation of the SME landscape. The data underwent rigorous analysis using Structural Equation Modelling (SEM), facilitated by SmartPLS software, to yield robust and comprehensive insights. The findings unequivocally reveal that organizational ambidexterity plays a significant mediating role in strengthening the linkage between entrepreneurial orientation and business performance. SMEs that adopt ambidextrous strategies—including scaling operations (lifting), market expansion (expanding), strategic collaborations (collaborating), resilience in adversity (surviving), continuous innovation (innovating), and operational stability (maintaining)—demonstrate notably superior performance outcomes compared to their counterparts that do not integrate such approaches. These results highlight the critical importance of adaptive strategies that effectively balance the optimization of internal resources with the exploration of external opportunities. In the dynamic and often volatile environments that typify developing economies, an organization’s ability to simultaneously explore new opportunities while exploiting existing capabilities emerges as a pivotal determinant of sustained success. The study offers practical insights for SME practitioners, underscoring the necessity of embedding ambidextrous frameworks within business models to enhance competitiveness, agility, and resilience in increasingly complex and unpredictable markets. In conclusion, organizational ambidexterity functions not merely as a bridge connecting entrepreneurial orientation and business performance but also as a catalyst for fostering organizational resilience and sustainable growth. This research contributes significantly to the broader understanding of how SMEs can thrive amid globalization and rapid market fluctuations, offering valuable implications for both academics and practitioners in the realms of entrepreneurship and business management.